Effectiveness Of Online Service System In The Office Of National Land Agency Of Semarang City - Delvi Amalia Rosa; Widya Pratiwi Asmara; Aryani Witasari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The research of